Effects of Lactobacillus acidophilus KLDS1.0901 on Proliferation and Apoptosis of Colon Cancer Cells - Yue, Yingxue; Wang, Song; Shi, Jialu; Xie, Qinggang; Li, Na; Guan, Jiaqi; Evivie, Smith Etareri; Liu, Fei; Li, Bailiang; Huo, Guicheng (Frontiers in Microbiology, 2022)
Colon cancer is the most common type of malignant tumor. The cytotoxicity effect of Lactic Acid Bacteria (LAB) may be active by inhibiting cancer cell proliferation, producing anti-cancer compounds, and inducing apoptosis in cancer cells, but the mechanism is unclear. Our previous study revealed that L. acidophilus KLDS1.0901 has good probiotic properties. In this study, we assessed the effects of L. acidophilus KLDS1.0901 on the proliferation of HT-29, Caco-2, and IEC-6 cells. Then, the apoptosis mechanism of HT-29 cells was studied when treated with L. acidophilus KLDS1.0901. Results showed that L. acidophilus KLDS1.0901 inhibited the proliferation of HT-29 and Caco-2 cells in a dose-dependent manner and reached the maximum under the condition of MOI=100 (rate of Lactobacillus to cells) at 48 h. With the increase of time and Multiplicity of Infection (MOI), Reactive Oxygen Species (ROS) in HT-29 cells, the apoptosis rate of HT-29 cells were increased, and the amount of blue fluorescence of the cells was also increased after Hoechst 33258 staining. Further research showed that L. acidophilus KLDS1.0901 reduced the mitochondrial membrane potential of HT-29 cells. Notably, 1133 differentially expressed genes were screened by transcriptomics research, including 531 up-regulated genes and 602 down-regulated genes. These genes were involved in the NF-κB and PI3K-AKT signaling pathways related to the apoptosis of HT-29 cells. These findings suggested that L. acidophilus KLDS1.0901 has the potential to be used in the development of a new type of functional foods for adjuvant treatment of colon cancer.